Effect of Social Capital and Support System on Health: A Review Article - Abrar H. Almutairi; Alyaa Farouk A. Ibrahim; Nagwa A. Afefy; Amel Dawod Kamel Goudia; Yulis Setiya Dewi (CV. Global Health Science Group, 2023)
Social capital is the resources, social help, information channels, and social accreditations inserted inside a singular informal community. As a result, social capital can also be seen as both an individual trait and a communal property in this approach. This literature review will examine the relationship between social capital and support system on human health. Therefore, the primary focus points will be social capital & support system its relationship to individual’s health. Participation in social groups has a normative influence on behaviors, often influencing whether people eat a healthy diet, exercise, smoke, drink, or use illegal substances.